“Ctrl + C, Ctrl + V”: Academic Integrity in Online Language Learning - Lorelyn A. Gabatin; Carmela May M. Loquias; Marlon M. Redondo; Dan Fereth Fajardo (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
This qualitative study aims to explore academic integrity in terms of plagiarism issues in online language classes at Camarines Sur Polytechnic Colleges. The study has two research questions: (1) What types of plagiarism do online submitted outputs of students in online language classes fall? (2) What strategies do college instructors use to prevent and detect plagiarism in their language classes? Turnitin and content analysis were utilized to identify types of plagiarism committed by students, while structured interviews and thematic analysis were used to gather data on strategies used by college instructors. Results indicated that among the five types of plagiarism, Badyal (2018) has categorized, Mosaic Plagiarism or Patch Writing was the most prevalent, while Structural Plagiarism had the least number of cases identified, and no instances of Self-Plagiarism were found. Nonetheless, some outputs were plagiarism-free. The study also identified language instructors' strategies to prevent and detect plagiarism in their classes. The study recommends that academic institutions prioritize creating a culture of honesty and ethical behavior in academic writing, educate students on clear citation guidelines, and implement stricter penalties. The study's results can assist policymakers and educational institutions create practical measures to encourage academic honesty and avoid plagiarism in online language classes.